Assessment of the Routine Functional Activities in the Comparative Siddha Medical Treatment for Symptomatic Knee Osteoarthritis in Jaffna District, Sri Lanka - Vinotha, S.; Ira, T.; Sri Ranjani, S. (Journal of Complementary and Alternative Medical Health (JOCAMAR), 2018)
Aims: Knee Osteoarthritis (KOA) is a most common form of the rheumatic disease and relatively the prevalence is higher in Asians than in Western populations. KOA is one of the five leading causes of disability among elderly men and women. The scope of this study was to assess the routine functional activities by WOMAC score in the Siddha medical treatment for symptomatic KOA in Jaffna District, Sri Lanka. Study Design: This was an open, randomized, parallel group of comparative clinical trial. Place and Duration of Study: This study was carried out in selected Government Ayurveda Hospitals in Jaffna District, Sri Lanka between January 2013 and August 2014. Methodology: This clinical trial was conducted based on American College of Rheumatology (ACR) classification, 837 KOA subjects were screened and 250 KOA subjects of both genders, aged ≥40 years were randomly selected at Out Patients Department of Ayurveda Hospitals. Selected subjects were alternatively divided into two groups as group A and group B. The group A were received ‘Medicine A’ {2 capsules of 1 g Amukkirai Chooranam with Thalangai ennai (external application)} while group B was received ‘Medicine B’ {2 capsules of 1g Vellarugu Chooranam with Thalangai ennai} twice daily, up to 40 days. The modified Indian version of Western Ontario and McMaster Universities Arthritis Index (WOMAC) score was the primary outcome variable used to assess the self-reported pain, stiffness and physical functions based on the life style activities. The collected data were analyzed by the SPSS version 17. Results: There were 177 (70.8%) female and 73 (29.2%) male with a mean age of 57.02 (SD±8.78) years. At the end of treatment, for group A, the mean total WOMAC score was reduced from 156.03±53.83 to 78.68±37.11 while for group B, that score was reduced from 165.29±57.19 to 83.79±41.08. Although there was a significant reduction in pain, stiffness, physical function and total score (P=0.000) for WOMAC index during routine functional activities at end of the treatment in each group, there was no significant differences (P>0.05) observed between both groups. Conclusion: The Present study also strengthens the contemporary area of comparative effectiveness of selected siddha medication (both Amukkirai Chooranam and Vellarugu Chooranam together with Thalangai ennai) in routine functional activities in the treatment of symptomatic KOA treatment over 40 days of therapy.
Keywords: knee osteoarthritis; life style; symptomatic